HIV-1 and SIV Predominantly Use CCR5 Expressed on a Precursor Population to Establish Infection in T Follicular Helper Cells - Xu, Yin; Phetsouphanh, Chansavath; Suzuki, Kazuo; Aggrawal, Anu; Graff-Dubois, Stephanie; Roche, Michael; Bailey, Michelle; Alcantara, Sheilajen; Cashin, Kieran; Sivasubramaniam, Rahuram; Koelsch, Kersten K.; Autran, Brigitte; et al. (Frontiers in Immunology, 2017)
Background: T follicular helper cells (Tfh) are increasingly recognized as a major reservoir of HIV infection that will likely need to be addressed in approaches to curing HIV. However, Tfh express minimal CCR5, the major coreceptor for HIV-1, and the mechanism by which they are infected is unclear. We have previously shown that macaque Tfh lack CCR5, but are infected in vivo with CCR5-using SIV at levels comparable to other memory CD4+ T cells. Similarly, human splenic Tfh cells are highly infected with HIV-1 DNA. Therefore, we set out to examine the mechanism of infection of Tfh cells. Methodology: Tfh and other CD4+ T cell subsets from macaque lymph nodes and spleens, and splenic Tfh from HIV+ subjects and tonsillar Tfh from HIV-uninfected subjects were isolated by cell sorting prior to cell surface and molecular characterization. HIV proviral gp120 sequences were submitted to genotypic and phenotypic tropism assays. Entry of CCR5- and CXCR4-using viruses into Tfh from uninfected tonsillar tissue was measured using a fusion assay. Results: Phylogenetic analysis, genotypic and phenotypic analysis showed that splenic Tfh cells from chronic HIV+ subjects were predominantly infected with CCR5-using viruses. In macaques, purified CCR5+ PD-1intermediate (int)+ memory CD4+ T cells were shown to include pre-Tfh cells capable of differentiating in vitro to Tfh by upregulation of PD-1 and Bcl6, confirmed by qRT-PCR and single-cell multiplex PCR. Infected PD-1int cells survive, carry SIV provirus and differentiate into PD-1hi Tfh after T cell receptor stimulation, suggesting a pathway for SIV infection of Tfh. In addition, a small subset of macaque and human PD-1hi Tfh can express low levels of CCR5, which makes them susceptible to infection. Fusion assays demonstrated CCR5-using HIV-1 entry into CCR5+ Tfh and pre-Tfh cells from human tonsils. Conclusion: The major route of infection of Tfh in macaques and humans appears to be via a CCR5-expressing pre-Tfh population. As the generation of Tfh are important for establishing effective immune responses during primary infections, Tfh are likely to be an early target of HIV-1 following transmission, creating an important component of the reservoir that has the potential to expand over time.